2020
DOI: 10.3390/nano10112311
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Bioactive Flowable Resin Composite Containing a Zinc-Doped Phosphate-Based Glass

Abstract: Flowable resins used for dental restoration are subject to biofilm formation. Zinc has antibacterial properties. Thus, we prepared a zinc-doped phosphate-based glass (Zn-PBG) to dope a flowable resin and evaluated the antibacterial activity of the composite against Streptococcus mutans (S. mutans) to extrapolate the preventative effect toward secondary caries. The composites were prepared having 0 (control), 1.9, 3.8, and 5.4 wt.% Zn-PBG. The flexural strength, elastic modulus, microhardness, depth of cure, io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 33 publications
1
51
0
Order By: Relevance
“…Moreover, these antibacterial monomer/drug/metal oxide NPs have no remineralizing ability, largely impeding their development as composite resins ( Cocco et al, 2015 ; Arun et al, 2021 ). Recently, promising alternatives such as bioactive ceramic particles [e.g., calcium phosphate nanoparticles (NACPs), bioactive glass (BAG), zinc-doped phosphate-based glass] have been exploited as inorganic fillers to construct orthodontic adhesives or composite resins, which have been found to achieve both antibacterial and remineralizing effects ( Liu et al, 2018 ; Par et al, 2019b ; Bhadila et al, 2020 ; Lee et al, 2020 ). Among bioactive ceramic particles, BAG has attracted increasing interest in dental applications such as toothpaste, dentin desensitizers, orthodontic adhesives, and experimental composite resins ( Wang et al, 2010 ; Yang et al, 2016 ; Al-Eesa et al, 2019 ; Aponso et al, 2019 ; Par et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these antibacterial monomer/drug/metal oxide NPs have no remineralizing ability, largely impeding their development as composite resins ( Cocco et al, 2015 ; Arun et al, 2021 ). Recently, promising alternatives such as bioactive ceramic particles [e.g., calcium phosphate nanoparticles (NACPs), bioactive glass (BAG), zinc-doped phosphate-based glass] have been exploited as inorganic fillers to construct orthodontic adhesives or composite resins, which have been found to achieve both antibacterial and remineralizing effects ( Liu et al, 2018 ; Par et al, 2019b ; Bhadila et al, 2020 ; Lee et al, 2020 ). Among bioactive ceramic particles, BAG has attracted increasing interest in dental applications such as toothpaste, dentin desensitizers, orthodontic adhesives, and experimental composite resins ( Wang et al, 2010 ; Yang et al, 2016 ; Al-Eesa et al, 2019 ; Aponso et al, 2019 ; Par et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%
“…X-ray fluorescence revealed that the zinc phosphate cement with the highest zinc oxide concentration had the largest zones of inhibition. In the literature, zinc oxide has been extensively studied for its ability to inhibit bacterial growth [19]. Other studies have found that zinc ions directly affect the bacterial proteins involved in transmembrane proton translocation.…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate C. albicans, both micro-llers and nano-llers have been proposed [21][22][23] . Among these inorganic materials, zinc ions, in particular, have been explored as an alternative to conventional antimicrobials in dental materials 24,25 .…”
Section: Introductionmentioning
confidence: 99%